Enfoque Ecosistémico De Las Lagunas Las Verdes (Tres), Provincia Santiago De Chuco – La Libertad - Zelada Pereda, Olenka Jane (2017)
The objective of this research is to determine the Green 1, green 2 and 3 green lagoons ecosystem approach; for which applied provisions of the National Protocol for the monitoring of the quality of surface water resources, for determination of physical, chemical and biological quality of water from these natural resources, there was also the use of the Drone for determination morphometric software; a research is added to this in the socio-economic aspect of the population surrounding resources, that presenting the INEI, as the aim is to determine its use or the care you this take the wetland and its conservation status. Was determined that 3 lagoons present some degree of high concentration of heavy metals, creating a medium that is inappropriate for some cultivation or exploitation, this by mining action close to them; in terms of chemical physical analysis 3 have an acid pH, average dissolved oxygen, but in its generality the lagoon Green 1 is in a bad state, step to an eutrophication in contrast to the Green 2 and green 3, those in that order presents a State of oligotrophy, information corroborated with biological factor - Macroinvertebrates. Keywords: focus on ecosystem, macroinvertebrates, wetlands, eutrophication and pollution.